"Did I just do that?"—Six‐month‐olds learn the contingency between their vocalizations and a visual reward in 5 minutes. (27th September 2021) - Keren‐Portnoy, Tamar; Daffern, Helena; DePaolis, Rory A.; Cox, Christopher M. M.; Brown, Ken I.; Oxley, Florence A. R.; Kanaan, Mona
Abstract: It has been shown that infants can increase or modify a motorically available behavior such as sucking, kicking, arm waving, etc., in response to a positive visual reinforcement (e.g., DeCasper & Fifer, 1980; Millar, 1990; Rochat & Striano, 1999; Rovee‐Collier, 1997; Watson & Ramey, 1972). We tested infants to determine if they would also change their vocal behavior in response to contingent feedback, which lacks the social, emotional, and auditory modeling typical of parent‐child interaction. Here, we show that in a single five‐minute session infants increase the rate of their vocalizations in order to control the appearance of colorful shapes on an iPad screen. This is the first experimental study to demonstrate that infants can rapidly learn to increase their vocalizations, when given positive reinforcement with no social element. This work sets the foundations for future studies into the causal relationship between the number of early vocalizations and the onset of words. In addition, there are potential clinical applications for reinforcing vocal practice in infant populations who are at risk for poor language skills.